2006
DOI: 10.1016/j.cbpa.2005.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Function and occurrence of facial flushing in birds

Abstract: So far overlooked as a pigment involved in visual communication, the haemoglobin contained in the blood of all birds is responsible for the red flushing colours in bare skin areas of some species. Our aim has been twofold: (1) to study sub-epidermical adaptations for blood circulation in two flushing species: the crested caracara (Polyborus plancus) and the hooded vulture (Necrosyrtes monachus), and (2) to provide the first compilation of avian species with flushing skin. The bare facial skin of both the carac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
82
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 30 publications
3
82
0
1
Order By: Relevance
“…Although birds, like primates, also show both haemoglobin-dependent red skin (Negro, Sarasola, Farinas, & Zorrilla, 2006) and structural blue skin (Prum & Torres, 2003), the majority of studies of bird colour focus on carotenoid or melanin-based plumage coloration (Hill, 2006). Furthermore, while most primate studies have examined colour itself, with the exception of the extent of red in mandrills and drills, badges of status in birds appear to be based more on the size of the colour patch than on colour itself (Senar, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although birds, like primates, also show both haemoglobin-dependent red skin (Negro, Sarasola, Farinas, & Zorrilla, 2006) and structural blue skin (Prum & Torres, 2003), the majority of studies of bird colour focus on carotenoid or melanin-based plumage coloration (Hill, 2006). Furthermore, while most primate studies have examined colour itself, with the exception of the extent of red in mandrills and drills, badges of status in birds appear to be based more on the size of the colour patch than on colour itself (Senar, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the relationship between body size and plumage colour heterogeneity has never been reported. If anything, previous papers tangential to this topic are those by Badyaev (1997a), who reported no effect of body size on overall plumage brightness of cardueline finches, Bretagnolle (1993), who reported that body mass was positively correlated with the proportion of white in albatrosses and Negro et al (2006), who reported an association between large size, dark plumage colour and facial flushing colouration. Furthermore, opposing natural and sexual selection pressures are often expressed by different colour components, the latter mainly favouring brighter colours (Hill 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the American goldfinch Carduelis tristis, bills of males held in captivity showed a significant decrease in brightness within 24 h, perhaps due to physiological stress (Rosen and Tarvin 2006). Rapid and ephemeral color changes in exposed facial skin, including ''flushing'' due to dilation of blood vessels, may also serve as a short-term signal in a number of avian families (Curio 2004, Negro et al 2006). …”
Section: Discussionmentioning
confidence: 99%